Skin Cell and Tissue Responses to Cross-Linked Hyaluronic Acid in Low-Grade Inflammatory Conditions - Benjamin Sanchez; Sandra Ferraro; Audrey Josset-Lamaugarny; Aurélie Pagnon; Charlie K. Hee; Lauren Nakab; Dominique Sigaudo-Roussel; Bérengère Fromy (International Journal of Inflammation)
Hyaluronic acid (HA), used in a variety of medical applications, is associated in rare instances to long-term adverse effects. Although the aetiology of these events is unknown, a number of hypotheses have been proposed, including low molecular weight of HA (LMW-HA) in the filler products. We hypothesized that cross-linked HA and its degradation products, in a low-grade inflammatory microenvironment, could impact immune responses that could affect cell behaviours in the dermis. Using two different cross-linking technologies VYC-15L and HYC-24L+, and their hyaluronidase-induced degradation products, we observed for nondegraded HA, VYC-15L and HYC-24L+, a moderate and transient increase in IL-1β, TNF-α in M1 macrophages under low-grade inflammatory conditions. Endothelial cells and fibroblasts were preconditioned using inflammatory medium produced by M1 macrophages. 24 h after LMW-HA fragments and HA stimulation, no cytokine was released in these preconditioned cells. To further characterize HA responses, we used a novel in vivo murine model exhibiting a systemic low-grade inflammatory phenotype. The intradermal injection of VYC-15L and its degradation products induced an inflammation and cell infiltration into the skin that was more pronounced than those by HYC-24L+. This acute cutaneous inflammation was likely due to mechanical effects due to filler injection and tissue integration rather than its biological effects on inflammation. VYC-15L and its degradation product potentiated microvascular response to acetylcholine in the presence of a low-grade inflammation. The different responses with 2D cell models and mouse model using the two tested cross-linking HA technologies showed the importance to use integrative complex model to better understand the effects of HA products according to inflammatory state.